2021
DOI: 10.1177/20531680211005225
|View full text |Cite
|
Sign up to set email alerts
|

Reassessing the public goods theory of alliances

Abstract: The public goods theory of alliances exerts substantial influence on scholarship and policy, especially through its claim that small alliance participants free-ride on larger partners. Prior statistical tests of free-riding suffer from model specification and generalizability problems, however, so there is little reliable and general evidence about this prediction. In this study, I address those limitations with a new test of the free-riding hypothesis. Using data on 204 alliances from 1919 to 2007, I examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
4
1
Order By: Relevance
“…The latter concluded that the pattern of free-riding and lack of response to heightened Russian defence spending probably encouraged the invasion, as NATO appeared divided. On the other hand, our results are in contrast with those of Alley (2021) who finds that free-riding behavior based on economic weight is unusual in alliance politics, which may be due to limits on security as a public good or bargaining between alliance members. Finally, the above empirical analysis consistently interprets the major geopolitical events of the examined period.…”
Section: S S S I Others O Thers I I Others M Mcontrasting
confidence: 99%
See 3 more Smart Citations
“…The latter concluded that the pattern of free-riding and lack of response to heightened Russian defence spending probably encouraged the invasion, as NATO appeared divided. On the other hand, our results are in contrast with those of Alley (2021) who finds that free-riding behavior based on economic weight is unusual in alliance politics, which may be due to limits on security as a public good or bargaining between alliance members. Finally, the above empirical analysis consistently interprets the major geopolitical events of the examined period.…”
Section: S S S I Others O Thers I I Others M Mcontrasting
confidence: 99%
“…In the case of NATO, free-riding is attributable to members' feeling of security, rather than size, with countries responding both to the growth in American military spending on the one hand, and the growth of Soviet spending on the other between 1956 and 1988. More recently, Alley (2021), who studies 204 alliances from 1919 to 2007, finds little evidence to support the free-riding hypothesis, attributing low defence spending to allied capability or efficiency gains from specialising in pooled military resources.…”
Section: Prior Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Theoretically, the concept of free riding is quite clear; yet its operationaliza-tion is not straightforward. 1 Researchers have mostly analyzed NATO. They have tried to capture free riding by looking at whether smaller members spend less on defence in proportion to GDP (Alley 2021; Kim and Sandler 2020); how countries respond to increasing military expenditure on behalf of the US (e.g., Spangler 2018); or whether and how NATO allies historically reacted to increased threats from potential adversaries, notably the Soviet Union (Plümper and Neumayer 2015).…”
Section: Existing Findingsmentioning
confidence: 99%